BRAZIL AND THE US IN THE FTAA NEGOTIATIONS – WHO WINS AND WHO LOSES? - Rodrigues, Ralph Santiago Leal de Camargo; Guanziroli, Carlos Enrique; dos Santos, Vanessa Cristina (Seven Editora, 2026)
This study analyzes the negotiation process of the Free Trade Area of ​​the Americas (FTAA), highlighting the leading role and divergent strategies between Brazil and the United States. Initiated in 1994, the proposal aimed at the economic integration of the continent, but faced significant obstacles arising from economic asymmetries and the lack of common objectives among the main actors. The article uses a bibliographic and documentary approach to evaluate the tactics adopted: while Brazil sought to strengthen Mercosur as an independent bloc and adopted a defensive posture to delay the agreement, the US aimed to consolidate its regional hegemony. With the definitive end of negotiations in 2005, the US resorted to bilateralism with countries on the Pacific coast and in Central America, while Brazil focused on South American institutionalization. The work concludes by presenting a synthesis of the distribution of costs and benefits of this regional integration for these two countries.